Pengaruh Metode Home Experiment Terhadap Hasil Belajar Kimia Siswa Pada Materi Ikatan Kimia - Indah Afriliani; Tonih Feronika; Aini Nadhokhotani Herpi (BADAN PENERBIT STIEPARI PRESS, 2024)
The stages of the Home Experiment method in this research use the guided inquiry stages, namely Orientation, Problem Identification, Hypothesis, Designing & Conducting an Experiment (Home Experiment), Analyzing data and Concluding. This research aims to determine the effect of the Home Experiment method on student learning outcomes in chemical bonding material. This research was carried out at Nurul Falah High School, North Jakarta in the 2022/2023 academic year. This research method is quasi-experimental with a nonequivalent control group design. The sampling technique uses purposive sampling technique. The total sample was 64 students consisting of 32 students from class X IPA 1 as the control class and 32 students from X IPA 2 as the experimental class. The instrument used is a multiple choice objective test on chemical bonds with 25 questions to measure learning outcomes. The results of the posttest hypothesis test using the independent sample test or t-test with a level of 5% obtained a significance value (Sig. 2-tailed) = <0.01, which means H1 is accepted. The results of the research show that there is an influence of the Home Experiment method on student learning outcomes in chemical bonding material